4D svetlobna mikroskopija živih celic - Furlan, Valentina (Matrika, 2023)
The observation of processes inside of living cells is key to the further development of medicine and biology. This article examines the techinques needed to capture such images in space and time, in other words in 4D. This type of imaging depends on fluorescent microscopes, so the first half of the article focuses on fluorescence and the basics of microscopy. In the second half it examines two new methods of fluorescent microscopy, which enables us to take faster and more precise images through the whole sample.
Keywords: fluorescenca; fluorescence; fluorescenčna mikroskopija; fluorescent microscopy; living organisms; luminiscenca; luminiscence; živi sistemi